Beyond growth rate 0.6: What drives Corynebacterium glutamicum to higher growth rates in defined medium. Issue 2 (24th September 2013) - Unthan, Simon; Grünberger, Alexander; van Ooyen, Jan; Gätgens, Jochem; Heinrich, Johanna; Paczia, Nicole; Wiechert, Wolfgang; Kohlheyer, Dietrich; Noack, Stephan
Abstract In a former study we showed that Corynebacterium glutamicum grows much faster in defined CGXII glucose medium when growth was initiated in highly diluted environments [Grünberger et al. (2013b) Biotechnol Bioeng]. Here we studied the batch growth of C. glutamicum in CGXII at a comparable low starting biomass concentration of OD ≈ 0.005 in more detail. During bioreactor cultivations a bi‐phasic growth behavior with changing growth rates was observed. Initially the culture grew with <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsqmww2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μˆ=0.61±0.02 h−1</alternatives> before the growth rate dropped to <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zsqmwvh" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />μˆ=0.46±0.02 h−1</alternatives>. We were able to confirm the elevated growth rate for C. glutamicum in CGXII and showed for the first time a growth rate beyond 0.6 in lab‐scale bioreactor cultivations on defined medium. Advanced growth studies combining well‐designed bioreactor and microfluidic single‐cell cultivations (MSCC) with quantitative transcriptomics, metabolomics and integrative in silico analysis revealed protocatechuic acid as a hidden co‐substrate for accelerated growth within CGXII. The presented approach proves the general applicability of MSCC to investigate and validate the effect of single medium components on microorganism growth during cultivation in liquid media, and therefore might be of interest for any kind of basic growth study. Biotechnol. Bioeng. 2014;111: 359–371. © 2013 Wiley Periodicals, Inc.